Assessment of pharmacokinetics and tolerability following single‐dose administration of molnupiravir in participants with hepatic or renal impairment - Kelly E. Duncan; Russ P. Carstens; Kristin L. Butterfield; Yoon Jin; Laura R. Inbody; Andrea K. Schaeffer; Catherine Z. Matthews; Tian Zhao; Shruti Patel; Brian M. Maas; Mickie H. Cheng; S. Aubrey Stoch (Clinical and Translational Science)
Abstract Individuals with chronic liver or kidney disease are at increased risk of severe COVID‐19. Molnupiravir is an orally administered antiviral authorized for the treatment of mild‐to‐moderate COVID‐19 in adults at risk of progression to severe disease. Two nonrandomized, open‐label, single‐dose, multicenter, phase 1 trials were conducted to investigate the effects of hepatic and renal impairment on the tolerability and pharmacokinetics of molnupiravir (800 mg) and its metabolite β‐D‐N4‐hydroxycytidine (NHC; NCT05386589/NCT05386758). The impact of renal impairment on urinary excretion of NHC was also assessed. The 90% CI for the geometric mean ratio of the plasma NHC area under the concentration–time curve (AUC) from zero to infinity was <2.0 for participants with moderate hepatic or severe renal impairment versus healthy mean‐matched controls. Comparable geometric mean values were observed for other pharmacokinetic parameters—including AUC from 0 to 12 h, AUC from zero to the last measurable concentration, and peak plasma concentration—in participants with moderate hepatic or severe renal impairment and in healthy mean‐matched controls. Urinary excretion of NHC was low in healthy participants and participants with severe renal impairment; renal clearance was numerically lower in those with renal impairment. In both trials, all adverse events were of mild or moderate intensity and resolved by study completion. There were no clinically relevant treatment‐related effects on other safety evaluations. Overall, molnupiravir was generally well‐tolerated, with similar pharmacokinetic profiles in participants with hepatic or renal impairment and healthy participants, supporting its use for treating COVID‐19 in these individuals without the need for dose adjustment.